Doira as a National Musical Instrument - Tursunov, Begzod (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the Uzbek national instrument - doira - a percussion instrument. Musical instruments that are designed to create a musical tone or specific resonant sounds and certain rhythmic structures; used to play music individually or as a group (various ensembles, orchestras, etc.). Each instrument has its own timbre, range, and expression. The quality of the sound of a musical instrument often depends on the shape, general structure, device, and material used of the particular instrument. From ancient times, musical instruments were made of reeds, bamboo, wood, stone, bone, metal, leather, silk, coconut, pumpkin and others. The sound can be changed with the help of additional tools, performance styles, and some musical ornaments. Its emergence dates back to the earliest periods of human history, and its development is associated with the development of the art of music and performance, as well as the development of technology in the production of musical instruments.